OS 25-04 THE CHANGES OF ARTERIAL STIFFNESS MONITORED WITH CARDIO ANKLE VASCULAR INDEX (CAVI) DURING RAISED INTRACRANIAL PRESSURE IN THE RABBIT. (September 2016) - Miyazaki, Chikao; Takahashi, Mao; Shimizu, Kazuhiro; Chiba, Tatsuo; Morisita, Takenori; Yamamoto, Tomoyuki; Sugo, Nobuo; Takahara, Akira; Shirai, Kohji
Abstract : Objective: Cardio ankle vascular index (CAVI) is reflecting stiffness of the arterial tree from the origin of aorta to the ankles. We observed elevated CAVI in patients who suffered from apoplexy attack. To clarify the role and the mechanism by which arterial stiffness elevated just after apoplexy attack, the effect of enhanced intracranial pressure (ICP) by injecting saline into the cisterna magna of the rabbit on blood pressure, CAVI and cervical blood flow, were studied. Furthermore the role of sympathetic nerve was studied. Design and Method: The system of measuring CAVI of the New Zealand white rabbit was set up. General anesthesia was performed by ketamine and xylazine, and the respirator was set. Intracranial pressure (ICP) was monitored using a catheter inserted into subarachnoid space via right frontal bone craniotomy. Saline (15 ml) was inserted to raise ICP. Ganglion blocker, hexamethonium (10 μg/kg/10 min, and 100 μg/kg/10min) was administered just before saline injection. Results: When saline was injected into the cisterna magna and ICP was raised over 20 mmHg at least, blood pressure (62 ± 7.43 → 135 ± 27.41 mmHg), and CAVI (3.3 ± 0.39 → 4.8 ± 0.89) were increased. The heart rate and blood flow of common carotid artery increased. When hexamethonium (10 μg/kg/10 min and 100 μg/kg/10min) was administered before raising ICP, enhanced IPP -induced blood pressure increase (123 ± 9.58, 90 ± 5.42 mmHg, respectively) and CAVI increase (4.3 ± 0.35, 4.0 ± 0.16, respectively) were inhibited dose-dependently. Conclusions: Raised ICP induced an increase of blood pressure accompanying with an increase of CAVI, suggesting that enhanced stiffness of muscle artery might partly induce high blood pressure. Blocking sympathetic nerve by hexamethonium diminished raised blood pressure and CAVI, indicating that ICP increase-induced blood pressure and CAVI increases were mediated by sympathetic nerve activation.